Veganism,virtue, and vigils : human-animal interactions, vegan activism, and social meanings in a Johannesburg-based non-profit organisation - Pieterse, Jimmy (University of Pretoria, 2025)
Dissertation (MSocSci (Anthropology))--University of Pretoria, 2024.